A robust optimum controller for suppressing radiated sound from an intelligent cylinder based on sliding mode method considering piezoelectric uncertainties. (December 2019) - Talebitooti, Roohollah; Darvish Gohari, Hamed; Zarastvand, Mohamadreza; Loghmani, Ali
In this study, a robust controller against the uncertainties in piezoelectric patches including sensor and actuator is designed based on sliding mode method to control the radiated sound from cylindrical shells. Accordingly, in order to extract and discretize the dynamic equations of a smart cylinder equipped with piezoelectric patches, the Hamilton's principle and the Rayleigh-Ritz method are, respectively, used . The radiated sound is estimated by the Kirchhoff-Helmholtz integral and the acoustic structural sensing method. Furthermore, an innovative approach is proposed on sliding mode control to model system uncertainties and design robust control signals against these disturbances. Using effective control signals for each mode is the applied methodology for establishing independent sliding surfaces. In fact, it is attempted to relate between actuator matrix determinant and system control ability in generating the efficient control signals and error reduction due to actuators uncertainties. By the aid of this relation, optimization of the actuators position according to the genetic algorithm is implemented. The obtained results show that by optimizing the actuators position not only the appropriate performance of the system in controlling the radiated sound from the structure is enhanced but also the essential control voltage for each actuator is significantly decreased.